Bacillus vallismortis TU-Orga21 blocks rice blast through both direct effect and stimulation of plant defense - Thepbandit, Wannaporn; Srisuwan, Anake; Siriwong, Supatcharee; Nawong, Siriwan; Athinuwat, Dusit (Frontiers in Plant Science, 2023)
Beneficial microorganisms are an important strategy for sustainable plant production processes such as stimulate root exudation, stress tolerance, and yield improvement. This study investigated various microorganisms isolated from the rhizosphere of Oryza sativa L. in order to inhibit Magnaporthe oryzae cause of rice blast, by direct and indirect mode of action. The results indicated that B. vallismortis significantly reduced M. oryzae mycelium growth and deformed the hyphal structures. The effects of biosurfactant B. vallismortis was studied against M. oryzae spore development. The dose of ≥5% v/v biosurfactant significantly inhibited the germ tubes and appressoria formation. Other biosurfactants were evaluated as surfactin and iturin A by Matrix-assisted laser desorption ionization dual time-of-flight tandem mass spectrometry. Under greenhouse conditions, priming the biosurfactant three times before M. oryzae infection significantly accumulated endogenous salicylic acid, phenolic compounds, and hydrogen peroxide (H2O2) during the infection process of M. oryzae. The SR-FT-IR spectral changes from the mesophyll revealed higher integral area groups of lipids, pectins, and proteins amide I and amide II in the elicitation sample. Furthermore, scanning electron microscope revealed appressorium and hyphal enlargement in un-elicitation leaves whereas appressorium formation and hyphal invasion were not found in biosurfactant-elicitation at 24 h post inoculation. The biosurfactant treatment significantly mitigated rice blast disease severity. Therefore, B. vallismortis can be a promising novel biocontrol agent which contains the preformed active metabolites for a rapid control of rice blast by a direct action against pathogen and by boosting plant immunity.